(untitled) (KYAMC Journal, 2025)
Background: Receptor study for carcinoma breast is now a common practice before neoadjuvant therapy. Human Epidermal growth factor Receptor 2 (HER2) overexpression acts as a predictive marker of tumor aggressiveness. Objective: To determine the association of HER-2 overexpression in relation to tumor size and stage of breast carcinoma. Materials and Methods: A cross sectional study was carried out in SSMC & Mitford Hospital from July 2008 to June 2010. 52 patients with primary breast carcinoma were selected. Clinical features and histopathological findings were studied. Size, stage and overexpression to HER-2 receptor were the primary variables. Chi-square test, Mann Whitney test and Odds Ratio were performed for data analysis. Results: Out of 52 patients, 38.5% were 41 – 50 years of age, and nearly 60% of the patients were in the premenopausal state. Over half (51.9%) of the patients had a history of contraceptive use and 21.1% of the patients had a family history of breast cancer. Overexpression of HER-2 (56.3%) was found to be significantly associated with lymph node positivity (p = 0.005). 52.6% of the advanced stage (stage IIIa – stage IV) tumors had overexpression of HER-2. 57.1% of tumor ≥5cm exhibited overexpression of HER-2 as opposed to only 16.7% of the tumor <5cm (p = 0.031). The risk of having HER-2 amplification was estimated to be 5-fold (95% CI = 1.3 – 18.6) higher in patients with larger tumors. Conclusion: In primary breast carcinoma with larger tumor and in stage III-IV are more often associated with HER-2 overexpression. So, patients in these group will be benefited from immunotherapy.